Side effect of using N95 mask on oxygen saturation, respiration rate and pulse rate of health workers in Jakarta - Wulandari, Shenda Maulina; Rahmawati, Apriana; Rohmah, Ulfa Nur; Pertiwi, Harizza (Media Keperawatan Indonesia, 2023)
The new normal era brings people new habits, one of which is wearing masks. The particulate respirator N95 mask (N95 mask) is the mask with the highest filtration, but there are some complaints regarding its use, one of which is difficulty breathing. Therefore, this study aims to determine whether there is an effect of using an N95 mask on oxygen saturation (SpO2), respiratory rate (RR) and pulse rate (PR). This study uses a convenience sampling technique with a sample size of 60 respondents. The research design used was a quasi-experimental design with a one-group pre and post-test design. Data analysis used the Wilcoxon test with p <0.0001, which means that there are differences in the results of SpO2, RR, and PR before and after using the N95 mask. Suggestions for health workers and policymakers in Indonesia to be able to apply the maximum hours of using N95 masks so that health workers avoid illness, disability, or discomfort which can maintain optimal performance.